Prediction of pathological stage in prostate cancer through the percentage of involved fragments upon biopsy - Dall'oglio,Marcos F. (2005)
INTRODUCTION: The need for defining the extension of disease in patients undergoing radical prostatectomy due to prostate adenocarcinoma is a relevant factor cure in such individuals. In order to identify a new independent preoperative factor for predicting the extension of prostate cancer, we assessed the role of the percentage of positive fragments upon biopsy. MATERIALS AND METHODS: A retrospective study compared the percentage of positive fragments on biopsy with the extension of disease as defined by the pathological examination of the surgical specimen from 898 patients undergoing radical prostatectomy due to clinically localized prostate cancer. RESULTS: On the univariate analysis, the percentage of positive fragments on biopsy showed a statistical significance for predicting confined disease (p < 0.001), which was found in 66.7% of the cases under study. Additionally, we observed that the total number of removed fragments exerts no influence on the extension of the disease (p = 0.567). CONCLUSION: the percentage of positive fragments is an independent factor for predicting the pathological stage of prostate adenocarcinoma, and the number of removed fragments is not related to the extension of the disease.